PENGARUH MODAL KERJA, TENAGA KERJA, JAM KERJA TERHADAP PENDAPATAN NELAYAN TRADISIONAL DI NAGARI KOTO TARATAK KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Trisnawati, Meta; Rosa, Yenni Del; Putri, Yosi Eka (Pendidikan Ekonomi, 2013)
Abstract This study aims to reveal (1) the effect of working capital on the traditional fishermenâs income, (2) the effect of labor on the traditional fishermens income, (3) the effect of working hours on the traditional fishermens income, (4) the effect of working capital, labor and working hours toward the traditional fishermens income. Fishermen are a group of people who are actively engaged in fishing activities, which directly or indirectly it depend on seafood.This study was conducted in September 2013. Types of the research is descriptive correlation study. The population of the research is located in the traditional fishing Nagari Koto Taratak. Samples taken in this study were 35 people by purposive sampling. Analysis of the independent and dependent variables through descriptive analysis and regression as well as to prove the hypothesis used the t test and F test.From the results of the analysis were obtained regression equation Log Y = 0.965 + 0.762LogX1 - 0,281LogX2 + 0.441 LogX3 + e with sig 0.000, 0.130 and 0.003. F test with a score of 815.476 sig . 0.000 < 0.05. Thus the variable capital income (X1), revenue hours (X3) partially significant effect on the income of traditional fishermen (Y), while the variable labor (X2) partially no significant effect on the income of traditional fishermen (Y). Simultaneously variables capital income (X1), labor (X2) and revenue hours (X3) significantly influence the traditional fishermens income (Y). Thus the results of this study are expected to provide benefits in formulating policies and strategies are effective and efficient in improving the traditional fishermenâs income Nagari Koto Taratak. Keywords: Fishermen working, capital income, labor, revenue hours